Bundengan : Between Aesthetics Expressivism, Social of Reality, and Perfomance Studies - Arbi, Bahtiar; Sumaryanto F, Totok; Utomo, Udi (Catharsis, 2017)
Bundengan is a transformation of kowangan or tudhung, which is a kind of head cover made of bamboo blades, clumpring, and rope fibers. This kowangan used to be used by duck herders to take shelter or shelter from the rain and the sun. The purpose of this study is to analyze: (1) The form of bundengan art performances; (2) Social reality that occurs in society; And (3) The aesthetic expression of artists bundengan with the flow of expressiveness. This research uses qualitative method with data collection technique of interview, observation and document study. The data validity technique is based on the credibility criteria, using triangulation of data. Data analysis techniques used are data collection, data presentation, data reduction, and data verification. The results show bundengan can replicate gamelan sounds such as bendhe, kempul, gong, and kendang applied in the pattern of the game, accompanying Lengger dance. There are three moments of dialectics in the social reality of externalization, objectivation, and internalization. Artists bundengan embrace the flow of aesthetic expressiveness art is not as a craft, magical, representation, and entertainment. The art of bundengan maintained its authenticity, and developed and disseminated.